Frozen in time : an epic story of survival and a modern quest for lost heroes of World War II - Zuckoff, Mitchell (New York : HarperCollins, 2013)
Mitchell Zuckoff account of a November 1942 B-17 search-and-rescue mission -- the harrowing crashes and the fate of the survivors and their would-be saviors at the Greenland Ice Cap. The author also recounts the efforts of the Coast Guard and North South Polar Inc. in 2012 to recover the remains of its crew.
Includes bibliographical references and index.
Keywords: United States. -- Army Air Forces -- Search and rescue operations; World War, 1939-1945 -- Aerial operations, American; Aircraft accidents -- Greenland; Search and rescue operations -- Greenland; Greenland -- Search and rescue operations